Analysis of the Use of Negative Clauses from the News "The Family of the Victims of the Lingga Kencana Vocational School Accident Called The Old Bus Was Unmaintained" - Nabila Nurul Azmi; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
Syntactic analysis of negative clauses has become an interesting research subject in the context of news analysis. Negative clauses in language often have complex structures and require in-depth understanding to decipher their meaning accurately. This research aims to analyze the syntax of negative clauses in news, with a focus on their syntactic structure and semantic function. The analysis method involves collecting news samples that contain negative clauses, then carrying out syntactic analysis of these clauses by paying attention to phrase structure, clause type, and their relationship to the news context. The research findings show significant variations in the syntactic structure of negative clauses depending on the type of news and the context. The results of the analysis provide new insights into how negative clauses are used in media language to communicate information effectively to readers. This research provides an important contribution to the understanding of the syntax and semantics of negative clauses in the news context.